1990
DOI: 10.1136/bjo.74.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of contact lens storage cases by Acanthamoeba and bacteria.

Abstract: In order to identify possible risk factors for microbial keratitis the storage cases for contact lenses of 102 asymptomatic lens wearers were tested for contamination by bacteria and free-living amoebae. Of this group 43 had significant counts ofviable bacteria and only 40 had negligible counts. Seven had contamination by acanthamoebae, of whom six also had significant bacterial counts. These results were categorised according to the type of contact lens worn and the lens disinfection method. The high rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(95 citation statements)
references
References 11 publications
5
87
0
3
Order By: Relevance
“…qualitative shift towards Gram-negative organisms, which constitute the majority of organisms isolated from lens storage cases and various in-use lens care solutions. [14][15][16] The observation that lens wearers did not yield sig nificantly more Gram-negative bacteria in this study may well reflect the efficiency of host antimicrobial defences at the ocular surface rather than fastidious attention to hygiene by the subjects studied.…”
Section: Discussionmentioning
confidence: 79%
“…qualitative shift towards Gram-negative organisms, which constitute the majority of organisms isolated from lens storage cases and various in-use lens care solutions. [14][15][16] The observation that lens wearers did not yield sig nificantly more Gram-negative bacteria in this study may well reflect the efficiency of host antimicrobial defences at the ocular surface rather than fastidious attention to hygiene by the subjects studied.…”
Section: Discussionmentioning
confidence: 79%
“…Another factor to consider is that individuals affected by keratoconjunctivitis sicca, or dryeye syndrome, should be considered at risk of suffering AK since the lack of natural tear flow could induce the growth of unusual pathogens on the ocular surface. Other authors have reported the presence of both pathogenic bacteria and Acanthamoeba in the eye and on contact lenses, among other sites, and even Pseudomonas aeruginosa has been reported to play an important role in the formation of biofilms for the attachment of Acanthamoeba strains to contact lenses (Barker & Brown, 1994;Larkin et al, 1990;Simmons et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Acanthamoeba thrive on bacterial colonies in culture, particularly on Gram-negative rods, and may reflect combined infection of the lenses or cases. 17,19,20 This sequence of events seems most likely where bacteria were isolated only days after the first symptoms were experienced. However, the cor neal ulceration seen in later-presenting acanthamoebal infection is a recognised risk factor for bacterial super infection.…”
Section: Discussionmentioning
confidence: 99%